ANALISIS STRATEGI PEMBELAJARAN UNIVERSAL DESIGN FOR LEARN-ING UNTUK ANAK BERKEBUTUHAN KHUSUS PADA SEKOLAH INKLUSI - Af'idatur Rosyidah; Dewi Nishwatul Fithriyah; Ira Rahmawati; Hafni Zukhrufina; Nurul Afidah (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2025)
Universal Design Learning (UDL) is a framework developed to improve access, engagement, and learning outcomes for all students, particularly in inclusive education. This study aims to analyze the concepts, principles, benefits, and challenges of implementing Universal Design for Learning strategies in inclusive schools. A qualitative approach with a literature review model was used in this study. Literature collection and analysis were conducted systematically by collecting and examining scientific sources such as national and international journal articles, academic books, and previous research related to UDL and inclusive education. The study results indicate that the implementation of UDL contributes to improving access to learning, engagement, learning motivation, and the ability of students with special needs to demonstrate academic understanding through various means of representation and expression. The implementation of UDL is needed in adaptable learning planning from the beginning, as well as policy support and competency development for educators to improve the quality of inclusive education implementation.